Sovereign Wealth Funds: Investors in Search of an Identity in the 21st Century - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2015)
Sovereign Wealth Funds (SWFs), as they have come to be known, are a hybrid type of foreign investor. They invest beyond their own borders with an aim to maximize returns as a foreign investor is expected to. At the same time, they are closely associated with governments, by ownership, source of funding, and/or investment objectives. Even as within this group, individual SWFs take various forms and may have divergent investment priorities and risk approaches. There is not even a universal definition of SWFs. As a result, they are often not viewed as typical foreign investors. The association of a SWF with a foreign government has raised various issues such as national security, trade protectionism and nationalism in the recipient countries. At the same time, due to the government ownership of some SWFs, they may fall into the group of business entities known as state-owned enterprises (SOEs). Given that SOEs are highly influential in some states, some recipient states have sought to subject SOEs to greater disciplines, such as in ensuring competition law and transparency principles apply to them, in order to level the playing field for other enterprises. Such disciplines have begun to appear in trade and investment treaties, and are coupled with the usual broad definitions of “investor” in such treaties. It is perhaps too early to state that there is a trend of greater legal and cross-border scrutiny over SOEs, and along with them, SWFs, in treaties. The Trans-Pacific Partnership Agreement that is under negotiation is an example of a potentially game-changing treaty which could affect SWFs qua SOEs. The challenge for SWFs is to carve a distinct identity in the twenty-first century, as more treaties that impose binding requirements arise. This article examines some recent developments, how SWFs may need to forge a unique identity and challenges of recipient states in balancing investment openness and the above concerns.